2004
DOI: 10.1111/j.0001-5172.2004.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative stellate ganglion blockade prevents tourniquet‐induced hypertension during general anesthesia

Abstract: Ipsilateral SGB attenuated the hyperdynamic response mediated by prolonged tourniquet inflation during knee arthroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We recruited elderly female patients for this study irrespective of the presence of hypertension or diabetes. Therefore, the outcome of this investigation could be clinically useful for the treatment of vulnerable patients compared with other studies using healthy subjects 5-7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recruited elderly female patients for this study irrespective of the presence of hypertension or diabetes. Therefore, the outcome of this investigation could be clinically useful for the treatment of vulnerable patients compared with other studies using healthy subjects 5-7.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a sample size of five per group was calculated as being needed to show a difference of maximum SAP through 25 and 30 mmHg (SD 9 mmHg) between groups with an α risk of 0.01 and a β risk of 0.1 7. However, we recruited 15 patients for each group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that TIH & tachycardia denote activation of the sympathetic nervous system in response to the development of tourniquet pain [16]. The aim of this study was to test the effectiveness of combined lumbar plexus block and sciatic nerve block in lessening TIH.…”
Section: Introductionmentioning
confidence: 98%
“…[5] In the past various drugs have been used prophylactically to decrease TIH like Clonidine [6] , ketamine [7] , magnesium [8] , and methods like stellate ganglion block have also been used for the same. [9] Although the mechanism of TIH is not well understood, the autonomic nervous system plays an important role. [10] Hence, dexmedetomidine, a potent a 2 -adrenoceptor agonist may prevent hyper adrenergic responses and can be of prophylactic value for tourniquet induced hypertension.…”
Section: Introductionmentioning
confidence: 99%